Heat-setting parameters optimisation of cotton/elastane fabric using response surface methodology - Huzaisham, Nur Athirah; Nasir, Siti Hana; Mohd Idris, Muhammad Khalis; Carolina Quintero Rodriguez, Carolina Quintero Rodriguez (Nispr, 2023)
The effect of heat-setting treatment on the performance of cotton/elastane fabric has been studied. Response surface methodology has been used to design the experiments where temperature (°C), time (s) and fabric width extension (%) are taken as factor variables. Fabric dimension (lengthwise and widthwise), fabric areal density and fabric tension decay are taken as response variables. The findings establish that the optimum heat-setting parameters are 190℃ temperature, 75s process time and 13.5% width extension. It is necessary to optimise the heat-setting parameters to achieve better fabric dimensional stability, as overheating damages and deteriorates some of the elastane filaments, resulting in reduced recovery properties after a certain temperature point.